MANAGEMENT OF HAEMATURIA IN A TERTIARY HEALTH INSTITUTION IN NIGERIA - ABHULIMEN, VICTOR; OFURU, VITALIS OBISIKE (International Journal of Health Sciences, 2022)
Purpose: Haematuria is a very important sign and symptom of a urological disease. It may be due to a urological malignancy. Careful history, physical examination, investigation and monitoring is necessary to identify cause and adequately treat patient with haematuria. This study aims to highlight the management of haematuria in Port Harcourt, Nigeria. Methodology: This was a retrospective study of patients who presented with visible haematuria between January 2012 and December 2021. The patients' history, physical examination findings, investigations and treatment received were analysed. The form of treatment received was noted. Findings: Three hundred and forty-six patients were evaluated. Two hundred and fifty-six (74%), seventy-two (20.8%) and eighteen (5.2%) patients presented within a week, between two and three weeks and above 3 weeks respectively. Twenty-seven (7.81%) patients had emergency surgery for haematuria. Sixteen of these had prostatectomy, 3 had TURBT/ chemotherapy, and eight had nephrectomy. The others were managed conservatively. Unique contribution to theory, practice and policy: Many patients with surgical haematuria present early. The commonest cause of haematuria is benign prostatic enlargement and the commonest emergency surgery is open prostatectomy. Haematuria is mainly managed conservatively. Careful monitoring of patients' vital signs is critical in identifying patients who begin to decompensate during conservative treatment. When the need arises, immediate surgical intervention should be carried out.